(untitled) (Agroindustrial Science, 2024)
The cultivation area of blueberries (Vaccinium corymbosum L.) has a significant growth worldwide due to its nutritional value, the growing global demand and its economic potential. In Peru, the production of this crop is mainly for export and one of the main producing areas is the province of Trujillo. The objective of the study was to characterize and describe the symptoms of pathogens causing fungal diseases in the blueberry crop. Samples were taken from plants showing necrotic streaks on the stem, leaves and fruit for microbiological analysis in the laboratory. Samples were processed by direct observation of symptoms and presence of signs, using a humid chamber to promote sporulation and PDA culture medium for fungal isolates. Pestalotia sp. causing leaf spot and stem blight, Thekopsora minima causing leaf rust, Botrytis cinerea causing gray mold on flowers and fruit, and Lasiodiplodia theobromae causing dieback were identified. To corroborate their identification, pathogenicity tests were performed. For the control of these diseases, it is recommended that an integrated management plan be implemented to reduce the conditions for pathogen development, thus avoiding short-, medium- and long-term economic losses in the blueberry crop.